A Report Card of the NGT at the End of Seven Years Since Establishment: The Present and Future Ahead. Issue 3 (3rd July 2018) - Tripathi, Swapnil
ABSTRACT: A concern toward environment protection has always been a topic of discussion in India. The impact of its preservation is such that it was a part of the election manifesto of leading political parties too. Bestowing such importance naturally gives rise to the question of its current state, i.e., whether preservation of environment has been successful or not. India known for its rock solid environment statutes lacked an expedient and effective redressal mechanism. After half-hearted attempts, it was the creation of the National Green Tribunal (NGT) that brought a ray of hope to the people that finally a much needed adjudicatory body was in place. The question that the author attempts to answer in the article is regarding the status of such an institution at the end of seven years of its existence, i.e., whether the NGT has achieved its desired purpose or not.